OPTIMALISASI FUNGSI EKOLOGIS RUANG TERBUKA HIJAU PUBLIK DI KOTA SURABAYA - Rita Ernawati (Emara: Indonesian Journal of Architecture, 2015)
Green open spaces is an important element in creating an impressive and qualified city in realizing ecological city in order of ecological city realization. The government policy related to the 30% proportion provision constitute the minimum size in an effort to ensure an urban development balance. The city of Surabaya has a very strong commitment in the developing public green spaces, especially in the physical and management. Although the green spaces development achievements in the city of Surabaya in general has been quite good, but it needs further study on the optimization of green spaces ecological functions. With a descriptive quantitative method, this study aim to assessing public green space in the city of Surabaya based on dominance aspects of green space and it quality (preservation). Green space ecological functions contribute to the quality improvement of groundwater, flood prevention, air pollution reduction, and supporting in micro-climate settings. In general, the analysis showed that the cemetery and garden as a part of the green space in the city of Surabaya has been implementing it ecological function optimally. The public green spaces quality improvement efforts, in order to optimize their ecological function, should be synergized with other programs such as biopore development, channel and rivers management, as well as good waste and private green spaces management by involving all relevant stakeholders. An optimal green space management at each region is a form of sustainable development implementation that can establish the smart, humanist and ecological city of Surabaya